Evidence for superconducting phase coherence in the metallic/insulating regime of the LaAlO3–SrTiO3 interface electron system. (25th January 2016) - Fillis-Tsirakis, E; Richter, C; Mannhart, J; Boschker, H
Abstract: A superconducting phase with an extremely low carrier density of the order of cm −2 is present at LaAlO3 –SrTiO3 interfaces. If depleted from charge carriers by means of a gate field, this superconducting phase undergoes a transition into a metallic/insulating state that is still characterized by a gap in the spectral density of states. Measuring and analyzing the critical field of this gap, we provide evidence that macroscopically phase–coherent Cooper pairs are present in the metallic/insulating state. This is characterized by fluctuating vortex–antivortex pairs, and not by individual, immobile Cooper pairs. The measurements furthermore yield the carrier-density dependence of the superconducting coherence length of the two-dimensional system.